Village Head Competence in Gender-Responsive Village Fund Management: A Systematic Literature Review - Andri; Anna Fatchiya; Siti Amanah; Sumardjo; Adi Firmansyah (GoAcademica Research & Publishing, 2026)
Gender-responsive village fund management remains a governance challenge in decentralized systems across developing countries, particularly Indonesia. Village heads, as primary actors in local development, are expected to integrate gender perspectives into budget planning, implementation, and evaluation. However, limited competence in gender-responsive budgeting (GRB) and persistent structural barriers continue to constrain equitable fund distribution. This study aims to synthesize existing literature on village head competence dimensions required for effective GRB implementation at the village level. A systematic literature review was conducted using databases including Scopus, Web of Science, and other indexed sources, resulting in the analysis of 45 relevant studies published between 2020 and 2026. Thematic synthesis identified four core competency dimensions: technical and financial management, leadership and communication, gender sensitivity, and strategic planning and coordination. Findings reveal that while technical competence receives the most policy attention, gender sensitivity and participatory leadership are equally critical yet underemphasized. Women's participation in village fund decision-making remains constrained by patriarchal norms, legal ambiguities, and limited access to governance forums. Institutional frameworks, including the Village Consultative Body (BPD), monitoring mechanisms, and digital governance tools, significantly shape GRB prospects. Effective capacity-building strategies must integrate technical training, institutional reform, and community engagement. This study contributes to the governance literature by synthesizing multidimensional competency requirements for gender-responsive village leadership and identifying priority areas for policy intervention.